Was ist Stenus rogeri Kraatz, 1857? Eine bibliographische und Typenstudie. 145. Beitrag zur Kenntnis der Steninen (Coleoptera: Staphylinidae). - Puthz, Volker (Contributions to Entomology = Beiträge zur Entomologie, 1974)
The revision of the types of Stenus rogeri Kraatz (Coleoptera: Staphylinidae) show that St. rogeri Kraatz, 1857, is the same as St. providus Erichson, 1839, and that St. rogeri sensu Fuss, 1859, et. auct. sequ. p. p. different from the St. rogeri Kraatz individuals. Different opinions of various authors of the St. rogeri are discussed, and it is demonstrated that St. providus Erichson is a very variable and videly distributed species with the following new synonyms: Stenus rogeri Kraatz, 1857, nov. syn.; Stenus deubeli L. Benick, 1913, nov. syn.; Stenus latus L. Benick ,1913, nov. syn. Nomenclatural Acts deubeli L. Benick, 1913 (Stenus), syn. n. of Stenus providus Erichson, 1839 latus L. Benick, 1913 (Stenus), syn. n. of Stenus providus Erichson, 1839 rogeri Kraatz, 1857 (Stenus), syn. n. of Stenus providus Erichson, 1839